Applied statistics for business and management using Microsoft Excel - Herkenhoff, Linda; Fogli, John (Springer New York Imprint: Springer, 2013)
Applied Business Statistics for Business and Management using Microsoft Exel is the first book to illustrate the capabilities of Microsoft Excel to teach applied statistics effectively. It is a step-by-step exercise-driven guide for students and practitioners who need to master Excel to solve practical statistical problems in industry. If understanding statistics isn't your strongest suit, you are not especially mathematically-inclined, or if you are wary of computers, this is the right book for you. Excel, a widely available computer program for students and managers, is also an effective teaching and learning tool for quantitative analyses in statistics courses. Its powerful computational ability and graphical functions make learning statistics much easier than in years past. However, Applied Business Statistics for Business and Management capitalizes on these improvements by teaching students and practitioners how to apply Excel to statistical techniques necessary in their courses and workplace. Each chapter explains statistical formulas and directs the reader to use Excel commands to solve specific, easy-to-understand business problems. Practice problems are provided at the end of each chapter with their solutions. Linda Herkenhoff is currently a full professor and director of the Transglobal MBA program at Saint Mary's College in Moraga, California, where she teaches Quantitative Analysis and Statistics. She is the former Executive Director of Human Resources for Stanford University. The first sixteen years of her career included various responsibilities within Chevron Corporation, primarily as a geophysicist. She has lived/worked/conducted research in over 30 countries and has spent time on all 7 continents. John Fogli is the Founder and President of Sentenium, Inc. John's business research methods have helped public and private industries better understand the involvement necessary to lead consensus solutions. He has facilitated over 500 survey projects in the areas of consumer, employee, political, and operation(s) research. He is a member of the Market Research Association and holds a Professional Research Certificate. He is currently a part-time faculty member with the Department of Business at Diablo Valley College and sits on the Executive Council for The Pacific Chapter of American Association for Public Opinion Research. He earned his B.S. from University of California, Berkeley and an MBA from the University of San Francisco.